Commissioning and performance testing of the first prototype of AlignRT InBore™ a Halcyon™ and Ethos™-dedicated surface guided radiation therapy platform. (December 2020) - Nguyen, Daniel; Farah, Jad; Barbet, Nicolas; Khodri, Mustapha
Highlights: AlingRT InBore™ is a novel SGRT solution for bore-based Linacs. Cameras caused no adverse effects on beam delivery or image quality. Sub-millimetric accuracy is achieved for inter and intrafraction motion management. Systems' stability and performance are not affected by Halcyon™ rotations. AlignRT InBore™ shall allow contactless DIBH treatments on Halcyon™. Abstract: Purpose: To commission and assess the performance of AlignRT InBore™, a Halcyon™ and Ethos™-dedicated Surface Guided Radiation Therapy (SGRT) platform which combines ceiling-mounted cameras for patient setup and bore-mounted cameras for in-bore tracking. Methods: To check the potential impact of InBore™ cameras on dose delivery, 16 SRS, H&N, breast and pelvis patients' quality assurance (QA) treatment plans were measured with/without AlignRT InBore™ and using ArcCHECK® and SRS MapCHECK®. Impact on image quality was determined using Catphan® 540 phantom and considering all available MV and CBCT protocols (head, breast, chest and pelvis). The stability, accuracy and overall performance of AlignRT InBore™ was assessed using an MV Cube and anthropomorphic phantoms. Results: Comparison of 2D dose distributions with/without AlignRT InBore™ showed no impact on treatment delivery for all 16 QA checks (p-value > 0.25). 2D and CBCT images showed no artefacts or change in the contrast-to-noise ratio, resolution and noise values measured with Catphan® 540. Anti-collision sensors were unaffected by the bore-mounted cameras. Additionally, AlignRT InBore™ cameras allowed for motion detection with sub-0.5 mm accuracy and sub-0.4 mm stability with surface coverage of >50 × 60 × 35 cc. Accurate transition (sub-0.3 mm) from virtual to treatment isocentres was achieved. Finally, Halcyon™ rotations during CBCT and beam delivery resulted in limited camera vibrations with translation uncertainty <0.5 mm in left-right and anterior-posterior directions and <0.1 mm in head-feet direction. Conclusion: AlignRT InBore™ provides SGRT setup and intrafraction monitoring capabilities with a performance comparable to standard SGRT solutions while having no adverse effect on Halcyon™.